Prescribing and Dispensing of Oral Isotretinoin and Noncompliance with Recommendations in France before and during the COVID‐19 Pandemic - Anaïs Havet; Aurélie Moskal; Cécile Payet; Jérôme Massardier; Bénédicte Lebrun-Vignes; Anne-Pierre Jonville-Béra; Marc Chanelière; Marie Viprey (Dermatology and Therapy)
Abstract Introduction The coronavirus disease 2019 (COVID-19) pandemic disrupted care organization in France, likely changing the use of oral isotretinoin and worsening noncompliance with recommendations. We described the number of dispensations of isotretinoin, use of teleconsultation, and noncompliance with recommendations, before and during the COVID period. Methods This nationwide cohort included all subjects with isotretinoin dispensation between 2019 and 2022, using data from the French Health Data System (SNDS). The pre-COVID period corresponded to 2019, and the COVID period to 2020, 2021, and 2022. The first lockdown took place between March and May 2020. We calculated the relative change in the number of total and first dispensations and the difference in the percentage of teleconsultation and noncompliance with recommendations, including treatment initiation by dermatology specialists, prescription renewal, and pregnancy testing (PT), for each month, using 2019 as the reference. PT compliance was assessed in women aged 11–50 years. Results A total of 2,020,624 dispensations were identified between 2019 and 2022, including 18.1% of first dispensations. Compared with the pre-COVID period, the number of total dispensations decreased (April 2020: −12.6%; May 2020: −9.7%), as did the number of first dispensations (March 2020: −18.3%; April 2020: −37.6%). Nevertheless, the number of total and first dispensations increased over the other months. The teleconsultation rate was close to 0 in the pre-COVID period and increased by 21.8% in April 2020. Noncompliance with treatment initiations by dermatologists increased throughout the COVID period compared with the pre-COVID period (mean: 2.2%; range: −0.5% to 5.5%). Noncompliance with prescription renewal and PT increased during the first lockdown (April 2020: 8.9% and 9.5%, respectively), and tended to stabilize thereafter. Conclusions The effect of the COVID-19 pandemic on isotretinoin use was mainly observed during the first lockdown. This study also highlights persistent noncompliance and the need to assess the new French communication actions.